The Role of Gaming Technologies in Overcoming Difficulties in the Perception of Russian Speech in Preschool Children (A Case Study of Preschool Educational Institutions in Uzbekistan) (Uzbekistan Open Conference, 2025)
The article examines the problem of overcoming difficulties in auditory perception of Russian speech in preschool children in an Uzbek-speaking language environment. The focus is on the didactic potential of gaming technologies as an effective tool for developing phonemic awareness, enriching vocabulary, and forming initial communicative competencies in Russian as a foreign language. The theoretical foundations of speech perception, specific difficulties characteristic of Uzbek-speaking preschoolers, as well as practical aspects of implementing didactic, role-playing and active games in the educational process are analyzed. The necessity of adapting gaming methods to the national-cultural context and the importance of methodological training of teaching staff are emphasized.